Management of fisheries associations and social responsibility in the productive chain - González-Cabo, Verena; Valencia Rodríguez, Marino; Bonilla Betancourt, Luis Ferney; Mosquera Mosquera, Omaira (HUMAN REVIEW. International Humanities Review / Revista Internacional de Humanidades, 2022)
Artisanal fishing and industrialized aquaculture involve interest groups in environmental and social sustainability to improve the well-being of communities. It is proposed to analyze the management of fishing associations using the “Triple income statement” model, to strengthen the productive chain in Buenaventura, Colombia. The qualitative-descriptive approach and a questionnaire on organizational learning are used. Corporate Social Responsibility, a reflection of processes, practices and learning, improves productivity and competitiveness, requiring the modernization of production systems, the formalization of activities in the production chain and good practices for the economic and environmental sustainability of the sector.